System-level hypothesis of dopamine imbalance in early multiple sclerosis - Caligiore, Daniele; Schirripa, Aurelia; Biggio, Monica (Frontiers in Neurology, 2025)
Multiple Sclerosis (MS) is a chronic autoimmune disorder of the central nervous system, with evidence suggesting that age-related brain changes may influence its progression. Clinically Isolated Syndrome (CIS) often marks an early phase of MS, with optic neuritis frequently presenting as a symptom. Despite recognition as an early indicator, the mechanisms driving optic neuritis and its contribution to MS progression remain unclear. Traditionally, immune-mediated inflammation has dominated MS research; however, emerging evidence highlights neurotransmitter dysregulation—especially involving dopamine—as a crucial factor in disease pathophysiology. The impact of dopamine imbalance on neural circuits and its role in advancing MS requires further investigation. This paper proposes a system-level, dopamine-based hypothesis to explain MS origins, focusing on early stages in CIS. Building on a review of recent literature linking dopaminergic dysfunction, neuroinflammation, and demyelination, the model suggests that optic nerve demyelination, as seen in optic neuritis, disrupts dopamine signaling, triggering a cascade of neural alterations that drive MS pathogenesis. By emphasizing dopamine role in CIS and early MS, this framework offers a novel perspective on the neurobiological mechanisms underlying the disease. This approach complements current research on neurotransmitter involvement in age-related conditions, expanding understanding of how neurotransmitter imbalances may influence MS and related disorders.